Comparative study on standard static packing pressure (SSPP) and standard proctor laboratory compaction methods / Doris Asmani Mat Yusof - Mat Yusof, Doris Asmani (2012)
The most recognizable development of compaction test is known as the Standard Proctor Test, which is used to estimate the density value of soils. However, the laboratory concept produced by Proctor (1933) has a few imperfections in determining the value of Maximum Dry Density (MDD) and Optimum Moisture Content (OMC). It also has some imperfections in application where the method that is applied in the field and laboratory to measure the density of soil are different. The compaction technique applied on the subgrade road layer for cohesive soil is by using roller compactor machine (static technique) while the technique that is applied in the laboratory is by dynamic compaction method. Thus, a new laboratory compaction method has been developed to determine the density, shear strength, and CBR values by using Standard Static Packing Pressure (SSPP) efforts in order to close the gap between laboratory and field data. In this study seven (7) types of soil based on plasticity chart were tested in several tests to obtain the important engineering parameter such as density (pd), water content (wc), shear strength (Cu), compaction energy (E) and CBR value of soils. Based on the laboratory results, it was found that the SSPP method is more practical and sensible than the dynamic compaction.